O erotismo mítico da ninfeta - Barros, Lindinês Gomes de (2007)
This dissertation establishes a viewpoint in the Social Cience Field of the Nymphs image in the romanesque construction of the twentieth century based in modern archaeology. Our literary corpus is constitututed by the book of the russian author callled Wladimir Nabokov entlited Lolita and the book Presença de Anita, from a brazilian author called Mario Donato. Both works had a singular repercussion involving an erotic conception wich was faced as pornographic and baffling. We appeal to Georges Bataille‟s and Foucault‟s discussion in order to observe it through an erotic viewpoint from an inner experience not submitted to normalizations. Such experiences provoke a feeling of something unknown and it reflects wild singularities proposed by Foucault and related with many misunderstanding things presented in institutions and cultures. Furthemore Bataille‟s conception about erotism will give us conditions to analyze nymphs‟ bodies in order to see themselves from their main characteristics, such as seduction and tempting and maligning forces. We still aim to focus the paradigm of mankind and nature in the direction presented by Edgar Morin. He analyzes some feelings that nymphs provoke and their relation between men and death. In adittion, we present in this issue some questions between culture and biology, focusing on the initial period of larva (wich means the beggining), bringing up what is ready to be born, a mythical and significant body shown in the media. Lolita in the cinema and A Presença de Anita in the TV was disturbing in society and it projected the possibility of a syntaxes of desire. It can has a symbolic purpose or it can be a kind of social and cultural phenomenon, wich is an object of representation. Our purpose is to immersion/emerge in the Nimphs‟s body with adventure and its risks at the same time in wich we are crossing frontiers